ENHANCING STUDENTS’ ENGAGEMENT AND ACTIVE LEARNING THROUGH FLIPPED CLASSROOM IN LITERATURE CLASS - Viska Violita; Markus Budiraharjo (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2022)
This study explored the students’ engagement and active learning that appeared in flipped classroom learning. A flipped classroom is one of the course delivery modes that can be used in the pandemic situation now. The purpose of this research was to analyze to what extent a flipped classroom enhances students’ engagement and active learning in Introduction to Educational English Literature class. This research has one research problem. The research problem was to what extent does a flipped classroom enhance students’ engagement and active learning in Introduction to Educational English Literature class? This research adopted qualitative descriptive analysis. The instrument of this research was the questionnaire that used the Likert scale. The results of this research showed that through implementing a flipped classroom model in the Introduction to Educational English Literature class, the students’ behavioral engagement, emotional engagement, cognitive engagement, agentic engagement, and active learning were enhanced. In this case, the students could engage in the discussion forum, complete the tasks, and participate actively in learning activities so that the students could achieve higher engagement and learning achievement in the Introduction to Educational English Literature class.